Mechanical and Water Barrier Properties of Inhomogeneous Clay Nano-Particles Reinforced Thermoplastic Starch - Stephen Emeka Ochei; Johnson Olumuyiwa Agunsoye; Henry Ekene Mgbemere; Kolawole Dayo Alonge (ABUAD Journal of Engineering Research and Development)
This research investigated the development of biodegradable bioplastic as a possible replacement for petroleum-based plastics, which constitute a serious environmental hazard. These hazards include but are not limited to flooding resulting from blocked sewage and danger to aquatic life in marine environments. The solution casting method was used to blend inhomogeneous kaolinite clay nano-particles with distilled water, starch, dilute acetic and nitric acids to produce different compositions of thermoplastic starch (TPS)/Clay composites with clay reinforcements ranging from 2.5 to 10 wt.%.  The composites were characterized using an X-ray diffraction (XRD), and the mechanical and water absorption properties were determined. The result revealed a 9-fold improvement in the tensile strength (0.72 MPa), flexural strength increased 5-fold (3.34 MPa), and hardness increased 2-fold (23.56 HVN) as well as a reduction in water absorption by 3-fold (6.63%) when compared to the control. Furthermore, the 10 wt.% clay content composite showed the highest mechanical properties. The significant improvement in the listed properties was attributed to a reduction in crystallinity and the formation of new chemical bonds between the thermoplastic starch and the nano-clay. It was observed that the properties of the composites can be further enhanced if a synchronized machine blender (such as an extruder) is employed.